Oral cavity and genetic abnormalities - Kochańska, Barbara; Kusiak, Aida (Journal of Stomatology, 2017)
Introduction. There are many genetically conditioned diseases which are reflected in the oral cavity. Some disorders within the mouth may suggest the occurrence of a genetic syndrome and their early diagnosis is of vital importance for further treatment. Aim of the study. To present abnormalities of soft and hard tissues, as well as occlusal anomalies especially multiple abnormalities in relationship to genetic syndrome. Conclusions. The knowledge of certain abnormalities seems to be very important from the point of view of dental professionals because this specific knowledge can contribute to directing diagnostics to some genetic syndrome and to implementing multi-specialist medical treatment.